2023
DOI: 10.3390/toxins15120687
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric Powder Counteracts Oxidative Stress and Reduces AFB1 Content in the Liver of Broilers Exposed to the EU Maximum Levels of the Mycotoxin

Neenu Amminikutty,
Veronica Spalenza,
Watanya Jarriyawattanachaikul
et al.

Abstract: The most frequent adverse effects of AFB1 in chicken are low performance, the depression of the immune system, and a reduced quality of both eggs and meat, leading to economic losses. Since oxidative stress plays a major role in AFB1 toxicity, natural products are increasingly being used as an alternative to mineral binders to tackle AFB1 toxicosis in farm animals. In this study, an in vivo trial was performed by exposing broilers for 10 days to AFB1 at dietary concentrations approaching the maximum limits set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Having in mind that oxidative stress plays a major role in AFB1 toxicity, natural products such as turmeric powder are increasingly being used as an alternative to mineral binders to ameliorate AFB1 toxicosis in farm animals or poultry ( 150 ). It was found that broilers exposed for 10 days to AFB1 at dietary levels of 0.02 mg/kg feed showed a significant increase in lipid peroxidation in the liver, which was completely reverted by the concomitant administration of turmeric powder given at feed levels of 400 mg/kg.…”
Section: Plant and Herbal Additives As A Safe Approach To Combat Harm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Having in mind that oxidative stress plays a major role in AFB1 toxicity, natural products such as turmeric powder are increasingly being used as an alternative to mineral binders to ameliorate AFB1 toxicosis in farm animals or poultry ( 150 ). It was found that broilers exposed for 10 days to AFB1 at dietary levels of 0.02 mg/kg feed showed a significant increase in lipid peroxidation in the liver, which was completely reverted by the concomitant administration of turmeric powder given at feed levels of 400 mg/kg.…”
Section: Plant and Herbal Additives As A Safe Approach To Combat Harm...mentioning
confidence: 99%
“…It was experimentally proved that turmeric powder counteracted such negative effects and simultaneously increased the hepatic gene expression of some antioxidant enzymes (e.g., CAT and SOD2) and decreased the liver content of AFB1 to undetectable levels. The authors suggested that turmeric powder could be an effective feeding strategy to ameliorate AFB1 related adverse effects in broilers ( 150 ).…”
Section: Plant and Herbal Additives As A Safe Approach To Combat Harm...mentioning
confidence: 99%
“…Turmeric powder was proven to relieve AFB1-induced toxicity in broiler chicken, increase the expression of CYP2A6 mRNA transcript, and reduce the expression of NF-E2-related nuclear factor 2 (Nrf-2) transcript. The expression of AFB1 was decreased by turmeric powder, by mechanisms including enhancement of the expression of ABCG2 mRNA in the duodenum [50]. AFB1 is known to cause damage to the immune system and spleen, and the protective role of the Penthorum chinese Pursh compound (PCPC) in this condition was reported to be preventive and medicinal acting via the JAK/STAT pathway of cell death in the spleen of broiler chicken [51].…”
Section: Afb1 In Animal Injury Models: Dosing and The Use Of The Modelmentioning
confidence: 99%